Neonatal Thyrotoxicosis with Tricuspid Valve Regurgitation and Hydrops in a Preterm Infant Born to a Mother with Graves' Disease - Stefani Doucette; Anne Tierney; Anne Roggensack; Kamran Yusuf (Thieme Medical Publishers, Inc., 2018)
Neonatal hyperthyroidism is rare disorder due to the passage of thyroid receptor antibodies (TRBs) from the mother to the fetus. Neonatal thyrotoxicosis can present in several ways and if unrecognized, can be fatal. We present a preterm neonate who developed fetal hydrops and tricuspid regurgitation in utero. The mother had a history of treated Grave's disease. The infant responded to maternal treatment antenatally and postnatal anti-thyroid treatment, with resolution of both the tricuspid regurgitation and hydrops. To our knowledge, this is the first case report of tricuspid regurgitation associated with fetal and neonatal thyrotoxicosis. Our case also highlights the importance of obtaining a detailed and accurate history in a mother with previous Grave's disease, even if treated.